2019
DOI: 10.5812/ijhrba.93481
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Mindfulness-Based Intervention on Risky Behaviors, Resilience, and Distress Tolerance in Adolescents

Abstract: Background: The adolescent faces rapid physical growth that is emotionally immature, in terms of limited experience, and fragile and vulnerable in cultural terms. The rate of change in this period is high that can cause various behavioral problems during this period. Objectives: The aim of this research was to explore the effectiveness of Mindfulness-Based Intervention on risky behaviors, resilience and distress tolerance among adolescents in juvenile correction and rehabilitation center. Patients and Methods:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…Although some individuals have higher trait levels of distress tolerance, the ability to tolerate distressing situations or psychological experiences can be fostered though skill building and mindfulness-based interventions (Lotan et al, 2013; Nila et al, 2016). Mindfulness based interventions also support emotional regulation, the ability to regulate one’s emotional reactivity, and can foster distress tolerance among adolescents (Broderick & Jennings, 2012; Hosseinian & Nooripour, 2019). Training white adolescents in mindfulness-based skills of present moment awareness and adopting a non-judgmental stance may foster their tolerance for negative emotions that arise from C1 and C2, which in turn may promote anti-racist behaviors.…”
Section: An Integrative Model For the Development Of Anti-racist Beha...mentioning
confidence: 99%
“…Although some individuals have higher trait levels of distress tolerance, the ability to tolerate distressing situations or psychological experiences can be fostered though skill building and mindfulness-based interventions (Lotan et al, 2013; Nila et al, 2016). Mindfulness based interventions also support emotional regulation, the ability to regulate one’s emotional reactivity, and can foster distress tolerance among adolescents (Broderick & Jennings, 2012; Hosseinian & Nooripour, 2019). Training white adolescents in mindfulness-based skills of present moment awareness and adopting a non-judgmental stance may foster their tolerance for negative emotions that arise from C1 and C2, which in turn may promote anti-racist behaviors.…”
Section: An Integrative Model For the Development Of Anti-racist Beha...mentioning
confidence: 99%
“…Mindfulness helps individuals become more self-aware, attentive and focused on the present, which can enhance their ability to cope with stress and challenges. 39 Resilience enables adolescents to persevere, adapt, and rise to the occasion when faced with difficult circumstances. 40 Our study revealed substantial and lasting improvements in mindfulness and resilience, with medium to high effect sizes immediately post-intervention and persisting at the 3-month follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…The psychometric properties have been tested in both Chinese and American adolescents, both with the retained 15 items of the original DTS, and the DTS has been confirmed as an effective scale for adolescents (Tonarely & Ehrenreich-May, 2020;You & Leung, 2012). Findings from studies of community adolescents using DTS are similar to those in adults, meaning that EDT is inversely correlated with health behaviours (Lin, 2022;Warren et al, 2020), emotional distress (Tonarely & Ehrenreich-May, 2020) and health outcomes (Kechter & Leventhal, 2019); also, offering appropriate interventions could enhance EDT in adolescents presenting with psychological or behavioural disorders (Hosseinian & Nooripour, 2019;Hutchison et al, 2023). Given that CPD causes 20%-49% of annual adolescent deaths an increasing threat to adolescent health worldwide including in Taiwan (Fu et al, 2014;Liu et al, 2022;Strong et al, 2021), and that DTS could detect significant impact of EDT on emotional distress, poor health behaviours, health outcomes and improvement of EDT via intervention in adolescents, using the DTS to examine EDT in CPD adolescents should be a critical research goal.…”
mentioning
confidence: 93%